Strategi manajemen kesiswaan di sekolah dasar tanpa guru bk: studi kasus di sd aisyiyah - Sakinah, Nur Imanis (Maliki Interdisciplinary Journal, 2025)
This article examines student management strategies in SD Aisyiyah, which operates without a formal Guidance and Counseling (BK) teacher. Through observation and interviews, it was found that the school has developed a collaborative internal system involving homeroom teachers, subject teachers, and the principal to address student issues. Problems are resolved step-by-step through internal discussion and parent involvement. Additionally, extracurricular activities and student monitoring books are used as tools for character development and behavior control. The findings indicate that even in the absence of a BK teacher, schools can create an effective mentoring environment. The article recommends training for non-BK teachers and strengthening the monitoring system as an alternative to basic counseling services in elementary schools.